AIRBORNE AND TERRESTRIAL GRAVITY DATA QUALITY ASSESSMENT (CASE STUDY: BALI ISLAND) - Putra, Widy
Measurement of gravity data in land areas in Indonesia has been carried out since the Dutch colonial era. The increasing need for gravity data in various scientific fields demands the availability of gravity data in Indonesia. One such application is to determine the Indonesian geoid model. For the purpose of geoid determination, gravity data must have high accuracy and spatial resolution and have a wide area coverage. Efforts to fulfill the need for gravity data to determine the geoid have been carried out using the terrestrial method. However, due to the various topographical conditions of Indonesia and it’s vastness, the data coverage and resolution is not yet dense enough. Measurement of gravity using the airborne method is one solution and has been implemented since 2008 to meet the objectives of measuring gravity to determine the geoid in Indonesia. The prerequisite of accurate and high-resolution geoid is gravity data with sufficient accuracy and well-spaced intervals. In this study, an assessment of terrestrial and airborne gravity datasets of which was carried out by the Geospatial Information Agency of Indonesia (BIG) on the Bali island was carried out which consisted of airborne and terrestrial gravity data. From the results of the analysis and quality test, it was found that each airborne and terrestrial gravity data still contained bias and blunders. For terrestrial gravity data, accuracy is obtained in the range of ±6 mGal. As for the airborne gravity data, from the results of the cross-over analysis, it was found that the difference in values at the cross-over points was still found to be quite significant with a range of -31.97 – 56.58 mGal at flying altitude. The problem faced in this case is more related to compliance with the airborne and terrestrial gravity data measurement procedures.